Strategi Guru Pendidikan Agama Islam dalam Menciptakan Pembelajaran yang Menyenangkan di SDN 095 Babakan Jati Kota Bandung - Andre Nabil Herdiana; Fikri Alfan Fadilah; Halimatussa’diyah Az-zahra; Hani Hadiati Pujawardani (Pascasarjana IAI Nasional Laa Roiba Bogor, 2025)
The background of this research stems from the low level of student interest in Islamic Religious Education (PAI), which is generally delivered through monotonous lecture-based methods. In fact, religious education plays a central role in shaping character and morals from an early age. This study aims to explore the strategies used by Islamic Religious Education (PAI) teachers in creating an enjoyable learning process at SDN 095 Babakan Jati, Bandung. The research employed a qualitative approach using a descriptive-analytical method. Data were collected through interviews, direct observation, and document analysis. The findings of this study indicate that the strategies implemented by PAI teachers at SDN 095 Babakan Jati, Bandung, to create an enjoyable learning environment include the use of creative approaches, such as utilizing visual and audio media (images, animations, and Islamic songs), involving students in relevant educational games, providing rewards, and fostering a warm and religiously nuanced classroom atmosphere.